Structural Stability and Reconfiguration of International Joint Ventures - Yan, Aimin (Journal of International Business Studies, 1998)
Previous research suggests that international joint ventures (IJVs) are inherently unstable and fragile. This view has failed, however, to explain why many IJVs have an extended longevity and stability. This paper draws on two contrasting perspectives from organization theory (structural instability and structural inertia) to trace both the destabilizing and stabilizing forces in IJVs, and argues that a complete understanding of an IJV's dynamic evolution requires consideration of both forces.